The influence of three fertilizers and preparation Gibrescol used as the foliage spraying on the growth and nutritional status of maiden apple trees in a nursery - SŁAWOMIR ŚWIERCZYŃSKI; ALEKSANDER STACHOWIAK (Agronomy Science, 2009)
The influence of three fertilizers and Gibrescol preparation used as the foliage spraying on the growth and state of nourishment of two cultivars of maiden apple trees in a nursery was compared. Foliar fertilizers did not have any significant influence on the growth of maiden trees, except the number of dwarf shoots of ‘Delikates’ cultivar. However, they considerably increased the number of formed flower buds. Gibrescol preparation significantly increased the height and number of long shoots of maiden trees of ‘Jonica’ and the dwarf shoots of ‘Delikates’ cultivar, compared to the control. At the same time it did not initiate the formation of flower buds. The effect of chemical agents, applied as the foliage spraying on the content of mineral elements in the leaves of maiden apple trees, cultivated in a nursery, was diverse. Only a significantly higher amount of nitrogen in the leaves of two apple tree cultivars after foliar use of urea was noticed. A significantly lower value of calcium was observed in the leaves of the two cultivars in the control combination, compared with the others considered in the experiment.